The Factors Contributing To The Failure of The Mebidangro Metropolitan Area In North Sumatra Province - Hidayat, Wahyu (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2026)
The Mebidangro Metropolitan Area (Medan–Binjai–Deli Serdang–Karo) was designated as a National Strategic Area through Presidential Regulation No. 62/2011 and reinforced by Presidential Regulation No. 81/2014 to serve as a regional growth hub and a strategic node in the Malacca Strait trade corridor. However, its development has not achieved optimal performance as a modern, integrated metropolitan area. This study examines the factors behind this underperformance by analyzing policy documents, existing conditions, and institutional arrangements. The methodology combines a review of national and regional spatial planning regulations, descriptive-qualitative analysis of demographic, economic, transportation, and environmental data, and a SWOT framework. The findings reveal key strengths, including a solid legal foundation, strategic geographic position, significant economic scale, and basic infrastructure. However, critical weaknesses persist, such as weak metropolitan governance, uncontrolled sprawl, limited public transportation, and spatial inequality between the core city and surrounding areas. The study concludes that the absence of a metropolitan authority, fragmented inter-jurisdictional planning, and inadequate spatial–transport integration are the main causes of underperformance. Strengthening metropolitan governance, adopting Transit-Oriented Development (TOD), and enhancing intergovernmental collaboration are crucial. Aligning these strategies with the 2025–2045 National Medium-Term Development Plan will be essential to realizing Mebidangro’s vision as a competitive and sustainable metropolitan area.